One Colorado night - Rock, Joanne (Rock, Joanne. Return to Catamount., 2022)
"After her parents' messy divorce--and her own bad breakup with rancher Ryder Wakefield--Jessamyn Barclay cut all ties to Catamount, Colorado. But the New York real estate guru is back, reuniting with her estranged siblings to claim their inheritance--and reuniting with Ryder to rekindle their undeniable fire. Now Jess is expecting his child. Will she give their relationship a real second chance, especially once she learns the secret he's been keeping about her father?"--Back cover.